HOx and NOx production in oxidation flow reactors via photolysis of isopropyl nitrite, isopropyl nitrite-d7, and 1,3-propyl dinitrite at λ = 254, 350, and 369 nm - A. T. Lambe; J. E. Krechmer; Z. Peng; J. R. Casar; A. J. Carrasquillo; J. D. Raff; J. L. Jimenez; D. R. Worsnop; D. R. Worsnop (Atmospheric Measurement Techniques, 2019)
Oxidation flow reactors (OFRs) are an emerging technique for studying the formation and oxidative aging of organic aerosols and other applications. In these flow reactors, hydroxyl radicals (OH), hydroperoxyl radicals (HO2), and nitric oxide (NO) are typically produced in the following ways: photolysis of ozone (O3) at λ=254 nm, photolysis of H2O at λ=185 nm, and via reactions of O(1D) with H2O and nitrous oxide (N2O); O(1D) is formed via photolysis of O3 at λ=254 nm and/or N2O at λ=185 nm. Here, we adapt a complementary method that uses alkyl nitrite photolysis as a source of OH via its production of HO2 and NO followed by the reaction NO + HO2 → NO2 + OH. We present experimental and model characterization of the OH exposure and NOx levels generated via photolysis of C3 alkyl nitrites (isopropyl nitrite, perdeuterated isopropyl nitrite, 1,3-propyl dinitrite) in the Potential Aerosol Mass (PAM) OFR as a function of photolysis wavelength (λ=254 to 369 nm) and organic nitrite concentration (0.5 to 20 ppm). We also apply this technique in conjunction with chemical ionization mass spectrometer measurements of multifunctional oxidation products generated following the exposure of α-Pinene to HOx and NOx obtained using both isopropyl nitrite and O3 + H2O + N2O as the radical precursors.